The personal potential impact of combat athletes on overcoming mental stress in the stressful situa-tion of competitive activity - Vladimirovich, 1Kuzovkin Viktor; Igorevna, Kharitonova Anna (International Journal of Psychosocial Rehabilitation, 2020)
The results of an empirical study regarding the personal potential impact of combat athletes on the ability to overcome mental stress during the preparation for the major competitions are presented. The study in-volves 40 female athletes, members of the first Russian women's team in sambo, judo and catch style, aged 21 to 35 years. Using discriminant analysis, the correlation between stress indicators in a stressful situation and the personal potential characteristics of athletes is exposed.